Key values for democratic governance innovation: Two traditions and a synthesis. (5th May 2021) - Hendriks, Frank
Abstract: This article advances our understanding of the key values for democratic‐governance innovation by integrating two important, yet divergent, discourses—the one on democratic innovations, the other on governance innovations—thus capitalizing on their mutually reinforcing potential. The result is an integrative framework of core values, related normative coordinates, and key questions for improving democratic governance. The integrative values framework refines our understanding of the fundamental value diversity surrounding democratic governance innovation, and facilitates, as a sensitizing framework, critical analysis, evaluation, and design thinking. The values framework integrates core values—inclusiveness, efficaciousness, appropriateness, resilience, and counterbalance—which are complementary but not without friction. Mindfulness of the fundamental value diversity is critical for handling democratic governance innovation in a more encompassing value‐sensitive way. For realistically applying the values framework, acknowledging the complementarities and tensions between core values, roads ahead are discussed stressing necessarily open and situated conversations.